2020
DOI: 10.1186/s13756-019-0661-9
|View full text |Cite
|
Sign up to set email alerts
|

High clonal diversity of ESBL-producing Klebsiella pneumoniae isolates from clinical samples in a non-outbreak situation. A cohort study

Abstract: Background: Klebsiella pneumoniae has been responsible for a large number of clonal hospital outbreaks. However, some epidemiological changes have been observed since the emergence of CTX-M enzymes in K. pneumoniae. Aim: To analyse the transmission dynamics of Extended Spectrum β-Lactamase-producing Klebsiella pneumoniae (ESBL-Kp) in an acute care hospital. Methods: In 2015 a prospective cohort study was conducted. All new consecutive adult patients with ESBL-Kp isolates in all clinical samples were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
4
9
0
Order By: Relevance
“…Considering the ESBL-producing K. pneumoniae isolates, the bla CTX-M-15 gene was the most commonly detected (66.7%) ( Table 2 ), similarly with the results obtained in different countries in clinical samples from humans [ 3 , 5 , 10 , 62 ] and pets [ 63 , 64 , 65 ]. Moreover, this gene was the most commonly detected in K. pneumoniae isolated from septicemias obtained from the same hospital of the present study (CHTMAD, Vila Real, Portugal) [ 5 ].…”
Section: Discussionsupporting
confidence: 84%
“…Considering the ESBL-producing K. pneumoniae isolates, the bla CTX-M-15 gene was the most commonly detected (66.7%) ( Table 2 ), similarly with the results obtained in different countries in clinical samples from humans [ 3 , 5 , 10 , 62 ] and pets [ 63 , 64 , 65 ]. Moreover, this gene was the most commonly detected in K. pneumoniae isolated from septicemias obtained from the same hospital of the present study (CHTMAD, Vila Real, Portugal) [ 5 ].…”
Section: Discussionsupporting
confidence: 84%
“…The clustering of CTX-M-15 producing ST405 isolates into a dominant PT was also in favor of its intra-hospital diffusion. Other groups reported hospital epidemics with ESBL-Kp ST405 producing CTX-M-15 [ 8 , 36 , 37 ]. Although this clone has been reported to produce both CTX-M-15 and a carbapenemase, all but one ST405 isolate of our collection were susceptible to carbapenems [ 38 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same study by Parsaie Mehr et al 70% of K. pneumoniae isolates were related to urine samples and 14% were extracted from tracheal samples [5]. In a prospective cohort study by Xercavins et al to analyze the transmission dynamics of extended-spectrum β-lactamase-producing K. pneumoniae, among 60 isolates, about 47% were extracted from urine samples and only one was from respiratory tract sample [12]. e study of biofilm formation and antibiotic resistance of K. pneumoniae isolates from clinical samples by Nirwati et al revealed that among 167 isolates, gathered from a tertiary care hospital, 51.5% were extracted from respiratory specimens [13].…”
Section: Discussionmentioning
confidence: 99%